Identification of a novel HLA‐A*02:06:01:02 allele in a Chinese individual by sequence‐based typing. Issue 6 (2nd November 2015) - Kwok, J.; Ho, J.C.Y.; Chan, Y.S.; Soormally, A.; Marsh, S.G.E.
Abstract: The new HLA‐A*02:06:01:02 allele differs from HLA‐A*02:06:01 by a C→G substitution in Intron 1.